(untitled) (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: Coronary artery disease (CAD) is increasingly prevalent among female population, particularly in South Asia, and a large number of female patients currently undergo coronary angiography for a variety of indications. The objective of this study was to investigate the clinical and angiographic characteristics of female patients undergoing coronary angiogram, in a tertiary cardiac center in Bangladesh. Methods: This retrospective observational study was conducted at Ibrahim Cardiac Hospital & Research Institute, Dhaka, Bangladesh during the period from 1st September 2005 to 31st August 2016. A total of 7,627 female patients who underwent coronary angiography were included. Obstructive coronary artery disease (CAD) was defined as a stenosis ≥70% in at least one of the three major coronary arteries or a stenosis ≥50% in left main stem. Result: Nearly two-thirds (64.4%) of patients comprised of age group of 41-60 years with mean age of the patients being 55.4 ± 10.2 years. Unstable angina (38.2%) was the commonest indication for coronary angiography followed by stable ischemic heart disease (25.1%), non-ST segment elevation myocardial infarction (12.8%), ST segment elevation myocardial infarction (9.3%), left ventricular failure (7.5%), post-myocardial infarction angina (6%) and atypical chest pain (1.3%). Over three quarters were hypertensive 68.3% were diabetic and 29% and dyslipidemiac. Over 40% of the patients were overweight and 20% were obese. On trans-thoracic echocardiography, 65.2% had normal left ventricular (LV) systolic function; 17.6% and 9.9% had mild and moderate LV systolic dysfunction respectively. Nearly 30% had normal epicardial coronary arteries on angiography, while 17.4%, 16.5% and 37.2% had triple vessel disease (TVD), double vessel disease (DVD) and single vessel disease (SVD) respectively. Following angiography, 33.4% were advised PCI, 30.2% optimal medical management and 15.3% CABG. A few (3.2%) were advised for revascularization either by CABG or PCI. Conclusion: Unstable angina is the most common indication for coronary angiography among Bangladeshi females. A clustering of risk factors for CAD such as hypertension, diabetes and overweight or obesity are observed in them. Of the obstructive CADs, SVD is the most frequent finding, indicating that females undergoing CAG are likely to have diffuse CAD, although left main disease is not uncommon in this population. Further comparative studies with matched male population are recommended to find the differences in clinical and angiographic findings with respect to sex. Ibrahim Card Med J 2017; 7 (1&2): 9-14